Interest rate pass-through and monetary policy asymmetry: A journey into the Caucasian black box - Rustam Jamilov; Balazs Egert (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper analyses the interest rate pass-through for five economies of the Caucasus - Armenia, Azerbaijan, Georgia, Kazakhstan, and Russia. Employing an autoregressive distributed lag (ARDL) specification to monthly data, we find that the interest rate pass-through is systematically incomplete and sluggish, probably due to macroeconomic instability and low banking sector competition. It is not clear whether pass-through has improved over time and asymmetric adjustment is found to characterize the pass-through only occasionally. Overall, our results show a considerable degree of cross-country heterogeneity in the size and speed of the pass-through.
Keywords: E43; E52; N25; 330; interest rate pass-through; asymmetric adjustment; Caucasus